Filatova E. V. Аbout some contradictions in the theory of speech making - Filatova E. V. (Philological Treatises, 2020)
In the article it is spoken about speech making and a minimal speech-making unit. The contradictions during its solution are highlighted. A syntagma is revealed as a real speech making and perception unit for both oral and written speech. Taking into account what units the speech is composed of, we may say, basing on these units it is perceived.